Regulating the future European hydrogen supply industry: A balancing act between liberalization, sustainability, and security of supply? - Alexander Scheibe; Rahmatallah Poudineh (The Oxford Institute for Energy Studies, 2023)
The future of the European hydrogen supply industry lies at the heart of the European Union's energy policy, demanding the reconciliation of conflicting interests in liberalization, sustainability, and security of supply. This paper analyses the unique challenges faced by the emerging hydrogen economy, including the lack of an established market, transportation and storage infrastructure, uncertainty about demand and supply, and the manufactured nature of hydrogen production. The main question addressed is how the EU can create a regulatory framework that enables the expansion of the hydrogen economy within the time frame required to meet the net-zero target, while ensuring a well-functioning integrated market. The paper argues that directly copying the liberalization model used in the gas and electricity sectors may not be suitable for hydrogen, and could lead to delays and uncertainties. Instead, it suggests combining existing provisions from natural gas and electricity regulations with novel elements tailored to the hydrogen supply industry. The first set of recommendations involves leveraging existing regulations to ensure non-discriminatory access to future hydrogen networks, fostering competition, and enhancing system resilience. Additionally, established instruments and institutions for European coordination should be extended to include hydrogen, promoting cross-border cooperation and integration between hydrogen and electricity. The paper also recommends new regulatory guidelines to address the unique characteristics of the hydrogen industry. It suggests aligning unbundling rules for hydrogen transport infrastructure with sustainability and security objectives, and exploring synergies with existing natural gas infrastructure while ensuring transparency and fair competition. Given the limited cost recovery potential of the nascent hydrogen market infrastructure, policymakers may need to depart temporarily from strictly cost-reflective tariff models, exploring alternative methods such as merged tariffs across different energy carriers, and public interventions such as grants, subsidies, or guarantees, to ensure sufficient infrastructure investments. Overall, the proposed approach aims to create a robust regulatory framework that facilitates the creation of the European hydrogen market while addressing the diverse goals of the EU's energy policy.
Keywords: 330; Demand; EU; Europe; Hydrogen; Infrastructure; policy; Supply